ANALISIS PENGARUH PROFITABILITAS, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN UMUR PERUSAHAAN TERHADAP STRUKTUR MODAL USAHA MIKRO KECIL DAN MENENGAH KERAJINAN KUNINGAN DI KABUPATEN PATI - Nugroho, Nur Cahyo (Management Analysis Journal, 2014)
The  purpose  of this study was to  determine  the  effect  of  profitability, sales growth,  firm size,  and  age  of  the company on the capital structure. The population in this study was 40 Micro, Small and Medium Enterprises (SMEs) in Pati regency brass handicrafts. Samples were taken using a sampling method that is saturated by using the whole population there is as much as 40 SMEs. Methods of data analysis used in this study is multiple linear regression. The results showed variable profitability pelelitian significant positive effect on capital structure, sales growth variable significant positive effect on capital structure, company size significantly negative on capital structure, and firm age significant positive effect on the capital structure. The conclusions of this study are variable profitability, sales growth, firm size, and firm age are all factors that determine the capital structure of SMEs. For further research in order to add some other variables than those used in this study in order to find a more varied results